Pola Komunikasi Antar Relawan Satu Amal Indonesia dalam Membangun Kepedulian Sosial di Kota Palembang - Fitriani Riski Ramadani; Eraskaita Ginting; M. Mifta Farid (Institut Nalanda, 2026)
The growing phenomenon of social activities among volunteers highlights the crucial role of communication in fostering social concern within society. In practice, communication among volunteers serves not merely as a means of information dissemination, but also as a medium for coordination, interaction, and strengthening relationships within the group. Effective communication cultivates solid cooperation among members and underpins the success of sustainable social initiatives. This study aims to investigate the communication patterns among volunteers and the supporting factors in building social concern within the Satu Amal Indonesia community in Palembang City. A descriptive qualitative method was employed in this research. Data were collected through interviews, observation, and documentation. The theoretical framework utilizes group communication theory, which emphasizes the significance of interaction, group dynamics, and the role of communication in forging collaboration and achieving shared objectives within an effectively organized social group. The findings reveal that the implemented communication patterns encompass both vertical and horizontal communication, operating effectively within the volunteer group. This communication is bolstered by factors such as solidarity, shared goals, and the members' communication proficiencies. Ultimately, these communication patterns successfully enhance volunteer participation and instill the value of social concern in the surrounding community..